Advanced membrane modifications for reverse osmosis fouling mitigation: mechanistic insights and practical applications - Liu Yang; Fangbo Zhao; Peng Lin; Caixu Wang; Zhiguo Li; Wennan Liu; Ruofan Wang; Yushi Mei; Hee-Deung Park (Desalination, 2026)

Ruddlesden–Popper La2CoO4 with surface hydroxyl engineering for efficient catalytic hydrolysis of organophosphate esters and in situ phosphate immobilization - Jinwei Wang; Yaling Dai; Ruihan Wang; Yi Liu; Xiangjun Yang; Fengzhi Jiang; Xia Luo; Siping Ji; Zhiguo Lin (Environmental Research, 2026)

Study on real-time forecast of tunnel fuel and electric vehicle fire states based on multimodal fusion learning - Chao Guo; Juncun Chen; Deyuan Kan; Xihao Lin; Zhiguo Yan; Yuxin Zhang (Tunnelling and Underground Space Technology, 2026)

Interaction between Zygosaccharomyces bailii and Schizosaccharomyces pombe enhances acetic acid reduction in Baijiu fermentation - Shuai Yuan; Yuan Yun; Zhiguo Liu; Shuang Xing; Jiajun Du; Qinghe Liu; Mingjian He; Jinqi Guo; Liangcai Lin; Cuiying Zhang (Food Research International, 2026)

Chemical Characteristics, Sources, and Transport Pathways of PM2.5 in a Mid-Altitude Industrial City of the Upper Yellow River Basin - Lin Yi; Juanjuan Qin; Yuanyuan Qin; Yuwei Gao; Jingnan Li; Xiaoying Su; Shuming Zhang; Zhiguo Rao; Jihua Tan; Peng Yi (Water, Air, & Soil Pollution, 2026)

A 13,100-year record of net primary productivity from subtropical China reveals shifting climatic and anthropogenic controls - Lin Zhao; Shanshan Meng; Zijian Liu; Tengwen Long; Zhiguo Rao; Haibin Wu (Anthropocene, 2026)

Comparative analysis of topsoil and moss pollen traps in central Hunan low mountains: Implications for modern pollen–vegetation calibration in subtropical China - Jingling Wen; Lin Zhao; Huihan Yang; Zhiguo Rao (Review of Palaeobotany and Palynology, 2026)

Sulfur-doped cyanobacterial biochar-supported Co-Fe spinel oxide with enriched oxygen vacancies: overcoming redox and electron transfer limitations in Fenton-like sulfadiazine removal - Chen He; Yaling Dai; Jinwei Wang; Zhiguo Lin; Linxin Zhao; Fengzhi Jiang; Xia Luo; Siping Ji; Xiangjun Yang (Bioresource Technology, 2026)

Intelligent dynamic fire alarm framework for road tunnels using traffic accident prior knowledge and multi-target detection - Xihao Lin; Yi Shen; Xi Jiang; Zirui Wang; Chao Guo; Yuxin Zhang; Hehua Zhu; Zhiguo Yan (Tunnelling and Underground Space Technology, 2026)

Intelligent decision support for tunnel fire incidents: integrating dynamic knowledge graph with large language models - Xihao Lin; Lifan Hu; Zhiguo Yan; Hehua Zhu; Xi Jiang (Tunnelling and Underground Space Technology, 2026)

Enhanced human activities disturbed vegetation since 3500 years ago in southern China - Lin Zhao; Zijian Liu; Xiaoxu Qu; Zhongwei Shen; Zhiguo Rao; Xianyong Cao (Science Bulletin, 2026)

Vegetation-hydrology coupling in subtropical China during the Younger Dryas: A quantitative reconstruction from high-resolution pollen records at Luoxiao Mountains - Lin Zhao; Jinlong Liang; Zijian Liu; Tengwen Long; John Dodson; Lidan Liu; Yunxia Li; Zhongwei Shen; Zhiguo Rao; Xiaojian Zhang; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Improving growth performance across multiple sheep breeds by targeting the MSTN gene using an enhanced Cas12i system - Bo Liu; Huanyu Song; Miao Yan; Yu Wu; Pengfei Li; Zhanqing Fan; Yufei Chen; Yangsheng Wu; Jiapeng Lin; Liqin Wang; Xiaoyu Niu; Kun Xu; et al. (Science China Life Sciences, 2026)

Mechanical and microstructural responses of yellow sandstone with prefabricated fissures to tailings water immersion - Wenyu Dong; Fei Lin; Zhiguo Xia; Jun Hu; Hailong Wang; Bing Chen; Tianqi Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Holocene precipitation/humidity change trend in subtropical southern China: Contrary results, analyses and prospective - Xiaoxu Qu; Yunxia Li; Zhongwei Shen; Lin Zhao; Siyu Wu; Zhiguo Rao (Quaternary Science Reviews, 2026)

Facile preparation and enhanced comprehensive performance of TFC nanofiltration membrane based on carboxylated graphene oxide/polyethersulfone substrate - Ying Ma; Anqi Liang; Fangbo Zhao; Chengbao Geng; Zhiguo Li; Liu Yang; Caixu Wang; Peng Lin; XiaoXiao Zhang (Journal of Environmental Chemical Engineering, 2026)

Real-time coastal disaster monitoring system for typhoon-induced wave overtopping - Ying-Tien Lin; Yiqun Ye; Zheng Kong; Ye Zhu; Xiangbing Kong; Zhiguo He (Natural Hazards, 2026)

Inhibitory activity and antifungal mechanism of venturicidin A against Pyricularia oryzae - Yinan Wang; Lin Qi; Fei Liu; Chentong Yan; Fuqiang Zhao; Zhiguo Yu (Pesticide Biochemistry and Physiology, 2026)

Adsorption mechanism of phosphate and arsenate in water by Al-doped Zr-based MOF and theoretical DFT study - Qiaoshu Zhou; Yewei Qiu; Wenjing Chen; Fan Lei; Hao Xiang; Fan Zheng; Zhiguo Lin; Xiangjun Yang (Journal of Environmental Sciences, 2026)

Monocyte-mediated mechanisms in idiopathic pulmonary fibrosis: opportunities for early intervention - Zhiguo Mao; Ying Liu; Chengfu Han; Xingyi Yang; Xiangke Lin; Shuo Tian; Mingsan Miao (Apoptosis, 2026)

Strong link in hydrogen isotope ratios between plant α-cellulose and source water for an alpine peatland in the Altai Mountains of northwestern China: Implications for palaeohydrological reconstructions - Fuxi Shi; Zhiguo Rao; Jiantao Cao; Chao Huang; Yunxia Li; Guanghui Lin (Journal of Hydrology, 2025)

Late Holocene temperature variability in northern Xinjiang (NW China) and its potential connection to the Atlantic Meridional Overturning Circulation - Ruijin Chen; Aifeng Zhou; Zhiguo Rao; Mingrui Qiang; Panpan Ji; Lin Chen; Haipeng Wang; Jianhui Chen (Quaternary Science Reviews, 2025)

Microbiomics and machine learning-assisted approaches reveal amino acid patterns in high-temperature Daqu - Chao Fang; Gailing Shi; Qing He; Shuang Xing; Peng Chen; Feng Shi; Zhiguo Liu; Ping Tang; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Systematic review of fire safety for long railway tunnels - Xihao Lin; Zhiguo Yan; Yi Shen; Yinxu Shao; Hehua Zhu (Tunnelling and Underground Space Technology, 2025)

Degradation of tetracycline dominated by non–radical pathway: Oxygen vacancies in CuFe2O4 as key triggering factors for enhanced peroxymonosulfate activation - Chen He; Jinwei Wang; Jinyang Liu; Yaling Dai; Qiqi Liu; Zhicun Zhou; Boxian Ren; Zhiguo Lin; Xiangjun Yang (Journal of Environmental Chemical Engineering, 2025)

One-pot hydrothermal synthesis of magnetic La-based composites for phosphate removal and recovery: Effect of Lanthanum forms and adsorption mechanism - Zhiguo Lin; Chen He; Yalin Dai; Jinwei Wang; Boxian Ren; Xiangjun Yang (Journal of Environmental Chemical Engineering, 2025)

Reducing arsenic mobilization in sediments: A synergistic effect of oxidation and adsorption with zirconium-manganese binary metal oxides - Xue Jiang; Youzi Gong; Jiaxing Xiong; Boxian Ren; Yewei Qiu; Zhiguo Lin; Ying Tang; Shixiong Wang; Xiaolong Wang; Cai Li; Xiangjun Yang; Shiming Ding (Water Research, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

Complex spatiotemporal heterogeneity in Holocene human activities revealed by pollen and Pb records from major monsoonal China - Xiaoxu Qu; Zhiguo Rao; Zhongwei Shen; Yunxia Li; Lin Zhao; Chao Huang (Anthropocene, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Degradable microplastics induce more soil organic carbon loss via priming effects: a viewpoint - Zhenyu Yang; Ying Sha; Amit Kumar; Zhiguo Yu; Junjie Lin; Yan Lei (Plant and Soil, 2025)

Sediments in Yangzonghai Lake after engineering treatment with ferric salt flocculation for arsenic mitigation: source or sink?? - Boxian Ren; Jinwei Wang; Yaling Dai; Chen He; Shixiong Wang; Xiangjun Yang; Zhiguo Lin; Conghai Zhang (Journal of Soils and Sediments, 2025)

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

A low-cost soft sensor for sewer flow monitoring — Learning from water level measurements in manholes - Ruozhou Lin; Ruihong Qiu; Lihan Hu; Yaxin Ding; Zhiguo Yuan (Water Research, 2025)

Urinary metabolic alterations associated with occupational exposure to metals and polycyclic aromatic hydrocarbons based on non-target metabolomics - Ping Lu; Rujian He; Yingjun Wu; Bizhi Wu; Hailing Li; Chang He; Meiqing Lin; Mengmeng Wang; Wenwen Cai; Xiantao Shen; Guiying Li; Zhiguo Cao; et al. (Journal of Hazardous Materials, 2025)

Drying-rewetting cycles decrease temperature sensitivity of soil organic matter decomposition - Junjie Lin; Wenling Zhang; Amit Kumar; Dafeng Hui; Changai Zhang; Shengdao Shan; Zhiguo Yu; Biao Zhu; Yakov Kuzyakov (Agricultural and Forest Meteorology, 2025)

Research on LSTM-PPO Obstacle Avoidance Algorithm and Training Environment for Unmanned Surface Vehicles - Wangbin Luo; Xiang Wang; Fang Han; Zhiguo Zhou; Junyu Cai; Lin Zeng; Hong Chen; Jiawei Chen; Xuehua Zhou (Journal of Marine Science and Engineering, 2025)
The current unmanned surface vehicle (USV) intelligent obstacle avoidance algorithm based on deep reinforcement learning usually adopts the mass point model to train in an ideal environment. However, in actual navigation, due to the influence of the ship model and the water surface environment, the training set is triggered. The reward function does not match the actual situation, resulting in a poor obstacle avoidance effect. In response to the above problems, this paper proposes a long and short memory network-proximal strategy optimization (LSTM-PPO) intelligent obstacle avoidance algorithm for non-particle models in non-ideal environments, and designs a corresponding deep reinforcement learning training environment. We integrate the motion characteristics of the unmanned boat and the influencing factors of the surface environment, based on the curiosity-driven set reward function, to improve its autonomous obstacle avoidance ability, combined with the LSTM network to identify and save obstacle information to improve the adaptability to the unknown environment; virtual simulation is performed in Unity. The engine builds a USV physical model and a refined water deep reinforcement learning training environment including a variety of obstacle models. The experimental results demonstrate that the LSTM-PPO algorithm exhibits an effective and rational obstacle avoidance effect, with a success rate of 86.7%, an average path length of 198.52 m, and a convergence time of 1.5 h. A comparison with the performance of three other deep reinforcement learning algorithms reveals that the LSTM-PPO algorithm exhibits a 21.5% reduction in average convergence time, an 18.5% reduction in average path length, and an approximately 20% enhancement in the success rate of obstacle avoidance in complex environments. These results indicate that the LSTM-PPO algorithm can effectively enhance the search efficiency and optimize the path planning in obstacle avoidance for unmanned boats, rendering it more rational.

Testing and improving brGMGTs-based paleotemperature estimates in peat sediments: Evidence from global surface peat samples and two well-dated Holocene peat cores in far Northwest China - Zhongwei Shen; Minghua Zhao; Tianyan Lin; Xiaoxu Qu; Haichun Guo; Jiantao Cao; Guodong Jia; Zhiguo Rao (Global and Planetary Change, 2025)

Combined ventilation mode in extra-long road tunnels: Energy efficient channel utilization with the inclined shafts - Xihao Lin; Zhiguo Yan; Yi Shen; Chao Guo; Lifan Hu (Building and Environment, 2025)

Preparation of nanocellulose-silk fibroin stiff hydrogel and high absorbing-low expansion xerogel via polysaccharide-protein interactions - Yue Ma; Tian Huang; Zhixing Hu; Juan Yu; Liang Liu; Lin Lin; Meijuan Chen; Ruoxian Jia; Xin Li; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2025)

The dynamic adjusted system of sea use fees: An empirical research on the sea use management in Zhejiang province - Guanqiong Ye; Zeben Lian; Chong Chen; Chunyu Lin; Zhiguo He; Weidong Shang; Yongchao Zheng (Regional Studies in Marine Science, 2024)

Meteorological effects of ventilation corridor in central urban areas: A case study of Wuhan - Xuesong Li; Kai Lin; Dan Cheng; Han Zou; Yulong Shu; Zhiguo Jin; Jiabei Zhu (Sustainable Cities and Society, 2024)

Influence of vegetation type on brGDGTs: Results from surface soils beneath sub-alpine forest and grassland under the same climatic conditions - Shikai Wei; Tianyan Lin; Yunxia Li; Jiantao Cao; Guodong Jia; Mingzhi Chen; Zhiguo Rao (Organic Geochemistry, 2024)

The Mutual Regulatory Role of Ferroptosis and Immunotherapy in Anti-tumor Therapy - Zhiguo Mao; Yilong Hu; Yinan Zhao; Xiaolei Zhang; Lin Guo; Xiaoran Wang; Jinying Zhang; Mingsan Miao (Apoptosis, 2024)
Ferroptosis is a form of cell death that is triggered by the presence of ferrous ions and is characterized by lipid peroxidation induced by these ions. The mechanism exhibits distinct morphological characteristics compared to apoptosis, autophagy, and necrosis. A notable aspect of ferroptosis is its ability to inhibit uncontrolled tumor replication and immortalization, especially in malignant, drug-resistant, and metastatic tumors. Additionally, immunotherapy, a novel therapeutic approach for tumors, has been found to have a reciprocal regulatory relationship with ferroptosis in the context of anti-tumor therapy. A comprehensive analysis of ferroptosis and immunotherapy in tumor therapy is presented in this paper, highlighting the potential for mutual adjuvant effects. Specifically, we discuss the mechanisms underlying ferroptosis and immunotherapy, emphasizing their ability to improve the tumor immune microenvironment and enhance immunotherapeutic effects. Furthermore, we investigate how immunotherapeutic factors may increase the sensitivity of tumor cells to ferroptosis. We aim to provide a prospective view of the promising value of combined ferroptosis and immunotherapy in anticancer therapy by elucidating the mutual regulatory network between each. Graphical Abstract Ferroptosis in the tumor microenvironment involves intricate crosstalk between tumor cells and immune cells. Through MHC recognition, CD8 + T cells activate the JAK1/STAT1 pathway in tumor cells, impairing the function of System Xc and reducing GSH and GPX4 expression to promote tumor cell ferroptosis. Additionally, activation of the STAT1-IRF1-ACSL4 pathway could also promote ferroptosis. The blockade of the antioxidant pathway in tumor cells induces ferroptosis, and the released DAMPs could promote DCs maturation through the cGAMP-STING-TBK1 pathway, leading to antigen presentation that activates CD8 + T cells. The release of DAMPs also induces the M1-type polarization of macrophages, which exerts an anti-tumor effect. The anti-tumor effects of CD8 + T cells could also be enhanced by blocking inhibitory immune checkpoints such as PD-1, PD-L1, CTLA4, and LAG3. Abbreviations: ACSL4, acyl-CoA synthetase long-chain family member 4; BH4, tetrahydrobiopterin; cGAMP, cyclic GMP-AMP; CTLA4, cytotoxic T lymphocyte-associated antigen-4; DCs, dendritic cells; DHFR, dihydrofolate reductase; DHODH, dihydroorotate dehydrogenase; GPX4, glutathione peroxidase 4; GSH, glutathione; HIF-1α, Hypoxia-Inducible Factor-1α;IFN-γ, interferon-γ; IRF1, interferon regulatory factor 1;IRP1, iron regulatory protein 1; JAK 1, janus kinase; LAG3, lymphocyte activation gene 3; MHC, major histocompatibility complex; NRF2, nuclear factor erythroid-2-related factor 2; PD-1, programmed death protein -1; PD-L1, programmed death ligand 1; PUFA, polyunsaturated fatty acid; ROS, reative oxygen species; STAT1, signal transducer and activator of transcription 1; STING, stimulator of interferon genes; TBK1, TANK-binding kinase 1 TLR2, toll-like receptor 2. This diagram was drawn by Figdraw ( www.figdraw.com ).

Hexabromocyclododecanes in soils, plants, and sediments from Svalbard, Arctic: Levels, isomer profiles, chiral signatures, and potential sources - Chenlu Lin; Honghua Li; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang; Guibin Jiang (Journal of Hazardous Materials, 2024)

Priming effects of surface soil organic carbon decreased with warming: a global meta-analysis - Hongxin Dong; Junjie Lin; Jiayu Lu; Lujun Li; Zhiguo Yu; Amit Kumar; Qin Zhang; Dan Liu; Beibei Chen (Plant and Soil, 2024)

Study on the Interactions Between Cisplatin and Cadherin by Fluorescence Spectrometry and Atomic Force Microscopy - Boyu Chen; Xitong Wang; Jixiang Sun; Yamei Lin; Hongxin Zhi; Kai Shao; Yujie Fu; Zhiguo Liu (Journal of Fluorescence, 2024)

Outstanding performance of magnetic La2O2CO3/Fe3O4 nanosheets for simultaneous removal of phosphate and arsenate from wastewater - Ding Chen; Chen He; Boxian Ren; Saiyue Yang; Yiman Ma; Zhiguo Lin; Xiangjun Yang (Journal of Water Process Engineering, 2024)

A novel ESIPT fluorescent probe for early detection and assessment of ferroptosis-mediated acute kidney injury via peroxynitrite fluctuation - Miao Chen; Shuiling Lin; Bingbing Tang; Tian Tian; Yahui Leng; Danwen Liu; Kelong Wang; Yi Geng; Zhiguo Luo; Li Shen; Tongsheng Chen (Analytica Chimica Acta, 2024)

Transmission characteristics and the factors influencing stable oxygen isotopes in precipitation, soil water, and drip water in Remi Cave, Western Hunan, China - Yiping Tian; Yunxia Li; Jiayan Li; Chenxi Yang; Angli Du; Miaofa Li; Xinping Zhang; Lin Zhao; Lidan Liu; Zhiguo Rao (Journal of Hydrology, 2024)

Experimental study of the lock-release gravity current propagates on a rough upslope - Jiufeng Ji; Dongrui Han; Yeping Yuan; Ying-Tien Lin; Zhiguo He (Environmental Fluid Mechanics, 2024)

Quantitative Holocene climate reconstruction and anthropogenic impact analysis based on the pollen records in peat sediment in Southern China - Lin Zhao; Yaoyao Zeng; Zhiguo Rao; Chao Huang; Yunxia Li; Lidan Liu; Chunmei Ma (Global and Planetary Change, 2024)

Sedimentary brGDGTs in China: An overview of modern observations and proposed land Holocene paleotemperature records - Tianyan Lin; Zhiguo Rao; Yaoyao Zeng; Yunxia Li; Lin Zhao; Lidan Liu; Xiong Xiao; Cicheng Zhang; Zhongwei Shen; Jiantao Cao; Guodong Jia (Earth-Science Reviews, 2024)

Natural and anthropogenic controls on environmental change during the Holocene based on a multi-proxy record obtained from subalpine peatland in southern China - Xiaoxu Qu; Chao Huang; Zhiguo Rao; Liyuan Wu; Yongyi Luo; Fajin Chen; YunXia Li; Lin Zhao; Lidan Liu; Zhiguang Song; Wenfeng Deng (Science of The Total Environment, 2024)

Holocene provenance variations and palaeofloods response to ENSO-driven monsoon precipitation in the subalpine peatland in southern China - Xiaoxu Qu; Chao Huang; Zhiguo Rao; Gangjian Wei; Liyuan Wu; Yongyi Luo; Yunxia Li; Lin Zhao; Lidan Liu; Wenfeng Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

Ocean decimeter-level real-time BDS precise point positioning based on short message communication - Fuxin Yang; Guochao Li; Jie Zhang; Zhiguo Sun; Ruizhe Zhang; Lin Zhao (GPS Solutions, 2024)

Phytolith-reconstructed Holocene vegetation dynamics from a subalpine peat deposit in the mid-subtropical zone of China - Lidan Liu; Hengyu Liu; Zhiguo Rao; Chao Huang; Lin Zhao; Yunxia Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Whole-genome sequencing and bacteriocin purification of Lactiplantibacillus plantarum HY41 conﬁrms bactericidal and probiotic potential - Hongbiao Li; Ting Liu; Xiuqin Zhang; Zhiguo Xiong; Qing Hong; Shuang Jia; Yi Lin; Liping Wang; Yueliang Zhao (International Biodeterioration & Biodegradation, 2023)

Polystyrene microplastic attenuated the toxic effects of florfenicol on rice (Oryza sativa L.) seedlings in hydroponics: From the perspective of oxidative response, phototoxicity and molecular metabolism - Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Siyi Zhang; Zhiheng Li; Zhiguo Fang; Yuezhong Wen; Huijun Liu (Journal of Hazardous Materials, 2023)

An Experimental Investigation into the Feasibility of a DC Hybrid Power Plant for a Northern Sea Route Ship - Yi Zhou; Kayvan Pazouki; Rose Norman; Haibo Gao; Zhiguo Lin (Journal of Marine Science and Engineering, 2023)
Increasingly, the melting of Arctic ice due to global warming has provided opportunities for commercial shipping between Asia and Europe. Given the vulnerability of the Arctic environment, especially due to emissions of short-lived pollutants from shipping activities, a more effective propulsion system with a comprehensive control strategy is required to reduce fuel consumption, thus potentially mitigating the impacts of shipping activities on the northern sea route (NSR). In this paper, a shipboard DC hybrid system powered by a combination of diesel generator sets and batteries is proposed and analysed in terms of its application on a ship in the NSR. The specific fuel consumption and various losses in the power sources were analysed to develop an efficiency-optimisation control strategy for the proposed DC hybrid power system. To evaluate the performance of the hybrid power system with the proposed optimisation control strategy, lab-scale experiments have been conducted in the Shanghai Marine Diesel Engine Research Institute to compare the proposed system with a conventional hybrid system. The experimental results indicate that the proposed DC hybrid power plant with the energy optimisation control contributes a 5.35% fuel saving compared with the DC fixed-speed diesel electric configuration during a scaled-down NSR scenario.

A GPU-accelerated and LTS-based 2D hydrodynamic model for the simulation of rainfall-runoff processes - Jingxiao Wu; Peng Hu; Zixiong Zhao; Ying-Tien Lin; Zhiguo He (Journal of Hydrology, 2023)

Priming effects induced by degradable microplastics in agricultural soils - Guohao Zhang; Dan Liu; Junjie Lin; Amit Kumar; Kaitao Jia; Xiaoxuan Tian; Zhiguo Yu; Biao Zhu (Soil Biology and Biochemistry, 2023)

Uncertainty of propagation and entrainment characteristics of lock-exchange gravity current - Yeping Yuan; Dongrui Han; Zhiguo He; Jie Xiong; Jiaxin Zhang; Yingtien Lin (Environmental Fluid Mechanics, 2023)

Estimation of forest aboveground biomass by using mixed-effects model - Haoning Feng; Qi Chen; Yueming Hu; Zhiguo Du; Guantu Lin; Changwei Wang; Youju Huang (International Journal of Remote Sensing, 2021)

Differential DNA Methylation Profiles in Patients with Temporal Lobe Epilepsy and Hippocampal Sclerosis ILAE Type I - Wang Zhang; Haiyang Wang; Binchao Liu; Miaomiao Jiang; Yifei Gu; Shi Yan; Xian Han; Alicia Y. Hou; Chongyang Tang; Zhenfeng Jiang; Hong Shen; Meng Na; et al. (Journal of Molecular Neuroscience, 2021)

Investigation of the effects of nonstationary features on rock joint roughness using the laser scanning technique - Yunfeng Ge; Zishan Lin; Huiming Tang; Binbin Zhao; Hongzhi Chen; Zhiguo Xie; Bin Du (Bulletin of Engineering Geology and the Environment, 2020)

What has caused the use of fertilizers to skyrocket in China? - Xiaohui Chen; Lin Ma; Wenqi Ma; Zhiguo Wu; Zhenling Cui; Yong Hou; Fusuo Zhang (Nutrient Cycling in Agroecosystems, 2018)

Comparative transcriptome analysis of Apis mellifera antennae of workers performing different tasks - Hongyi Nie; Shupeng Xu; Cuiqin Xie; Haiyang Geng; Yazhou Zhao; Jianghong Li; Wei-fone Huang; Yan Lin; Zhiguo Li; Songkun Su (Molecular Genetics and Genomics, 2018)

Preliminary analysis of spatiotemporal pattern of global land surface water - Xin Cao; Jun Chen; LiJun Chen; AnPing Liao; FangDi Sun; Yang Li; Lei Li; ZhongHui Lin; ZhiGuo Pang; Jin Chen; ChaoYing He; Shu Peng (Science China Earth Sciences, 2014)

A study of N-methyl-D-aspartate receptor gene (GRIN2B) variants as predictors of treatment-resistant major depression - Chen Zhang; Zezhi Li; Zhiguo Wu; Jun Chen; Zuowei Wang; Daihui Peng; Wu Hong; Chengmei Yuan; Zhen Wang; Shunying Yu; Yifeng Xu; Lin Xu; et al. (Psychopharmacology, 2014)

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon - Huawei Duan; Zhini He; Junxiang Ma; Bo Zhang; Zhiguo Sheng; Ping Bin; Juan Cheng; Yong Niu; Haiyan Dong; Han Lin; Yufei Dai; Benzhan Zhu; et al. (Archives of Toxicology, 2013)

Heavy Metal Contamination in the Water-Level Fluctuating Zone of the Yangtze River within Wanzhou Section, China - Junjie Lin; Chuan Fu; Xudong Zhang; Kun Xie; Zhiguo Yu (Biological Trace Element Research, 2012)

Spatial distribution and health risk of heavy metals and polycyclic aromatic hydrocarbons (PAHs) in the water of the Luanhe River Basin, China - Yongli Li; Jingling Liu; Zhiguo Cao; Chao Lin; Zhifeng Yang (Environmental Monitoring and Assessment, 2010)